2022
DOI: 10.1021/acssynbio.2c00355
|View full text |Cite
|
Sign up to set email alerts
|

A User’s Guide to Golden Gate Cloning Methods and Standards

Abstract: The continual demand for specialized molecular cloning techniques that suit a broad range of applications has driven the development of many different cloning strategies. One method that has gained significant traction is Golden Gate assembly, which achieves hierarchical assembly of DNA parts by utilizing Type IIS restriction enzymes to produce user-specified sticky ends on cut DNA fragments. This technique has been modularized and standardized, and includes different subfamilies of methods, the most widely ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 89 publications
(149 reference statements)
0
38
0
Order By: Relevance
“…into one ordered expression clone to be used for transgenesis (Fig. 1) (Bird et al ., 2022). Among the developed modular cloning methods, the Golden Gate system has emerged as the most widely utilized version, and in 2013 Lampropoulos et al .…”
Section: Introductionmentioning
confidence: 99%
“…into one ordered expression clone to be used for transgenesis (Fig. 1) (Bird et al ., 2022). Among the developed modular cloning methods, the Golden Gate system has emerged as the most widely utilized version, and in 2013 Lampropoulos et al .…”
Section: Introductionmentioning
confidence: 99%
“… Note: To simplify high throughput plasmid generation, the shuttle vectors used by the authors include BsaI restriction sites that are compatible with modular Golden Gate cloning. 4 Maps of backbone plasmids used by the authors are indicated in Figure 1 . These plasmids and their nucleotide sequences are available through Addgene.…”
Section: Before You Beginmentioning
confidence: 99%
“…While labs have employed these enzymes to manipulate DNA for the last several decades 5,6 , a major development in their use came in 2008 when Engler et al established a cloning method using the Type IIs enzyme BsaI, which they called Golden Gate assembly 7 . Since then, the method's popularity has grown [8][9][10] , due in part to its ability to connect fragments in a specific order and without a restriction scar 11 .…”
Section: Introductionmentioning
confidence: 99%